Characterization of gas-liquid flows in stirred vessels using pressure and torque fluctuations - Khopkar, A. R.; Panaskar, S. S.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2005)
Gas-liquid flows in a stirred vessel exhibit different flow regimes and demonstrate complex interaction of transport processes with varying spatio-temporal scales. The knowledge of key space and time scales of fluid dynamics is important for designing and enhancing the performance of gas-liquid stirred reactor. The present study uses simple, robust, and nonintrusive experimental techniques (torque and pressure sensors) to characterize the fluid dynamics in a gas-liquid stirred vessel. Time series obtained from the pressure and torque sensors were analyzed to develop criteria for flow regime identification. Further analyses of torque and pressure time series were done to extract valuable information of different time scales of fluid dynamics. The detailed analysis of torque and wall pressure fluctuations provided not only an insight into the fluid dynamics but also a possible opportunity to on-line monitoring of gas-liquid flows in stirred vessel.

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
7th International Conference on Fluid Mixing, London, ENGLAND, APR 10-12, 2006
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

Computational fluid dynamics simulation of the solid suspension in a stirred slurry reactor - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
A comprehensive computational fluid dynamics CFD model was developed in the present study to gain insight into the solid suspension in a stirred slurry reactor. The preliminary simulations highlighted the need for the correct modeling of the interphase drag force. A two-dimensional model problem was then developed using CFD to understand the influence of free stream turbulence on the particle drag coefficient. The proposed correlation was then incorporated in a two-fluid model (Euler-Euler) along with the standard k-epsilon turbulence model with mixture properties to simulate the turbulent solid-liquid flow in a stirred reactor. A multiple reference frame approach was used to simulate the impeller rotation in a fully baffled reactor. A computational model was mapped on to a commercial CFD solver FLUENT6.2 (of Fluent Inc., USA). The model predictions were compared with the published experimental data of Yamazaki et al. [Powder Technol. 1986, 48, 205] and Godfrey and Zhu [AIChE Symp. Ser. 1994, 299, 181]. The predicted results show reasonably good agreement with the experimental data. The computational model and results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound